Detecting Fake Accounts on Social Media (International Journal of Food and Nutritional Sciences, 2022)
Social media platforms are continuously more prevalent in the current generation, and they are becoming more and more ingrained in people's social life. To communicate with one another, they use Online media, exchange information, schedule events, and even operate on their own online businesses. Due to OSNs' quick expansion and the vast amounts of personal information, they have access to about their users, hackers and imposters have been drawn to them to steal personal information, propagate fake information, and engage in other illegal actions. On the other side, academics are now looking towards effective methods for spotting suspicious activity and bogus accounts that rely on account attributes and methods for classifying. Although a few of the properties of the profile that are utilized have an adverse effect on outcomes will have no impact at all in it. Additionally, using unbiased classification algorithms doesn't really produce satisfactory outcomes.